Determinantes de insolvência bancária no Brasil: identificação de evidências macro e microeconômicas - Aita, Jaqueline (Universidade do Vale do Rio do Sinos, 2010)
The banks are risks inherent in their goals of financial intermediation spawned directly in financial and productive flows citizens. The goal of this research was to identify in advance determinants economical and financial insolvency of commercial and multiple Brazilians banks in the period from July 1994 to June 2009 and propose early warning models. The models were built based on a sample composed 343 banks, being 83 insolvents and 260 solvents. The econometric techniques used for construction of models were the logistic regression analysis panel data fix effects and pooled The macroeconomic evidence describing the economic environment of which contributed to the insolvency: the decrease in interest rates, declining balance of trade exchange rates, the increase of financial crises, the positive variation of means of payment and the fall of credits in the economy. About the microeconomic evidence, contacts the downfall of liquid in national and exchange currency, for reduction of assets and liabilities and
Keywords: dados em painel; regressão logística; riscos bancários; falências bancárias; banking risks; logistic regression; panel data; bankruptcy bank; Ciências Sociais Aplicadas